Cardiovascular risk management system: prerequisites for developing, organization principles, target groups - E. V. Shlyakhto; N. E. Zvartau; S. V. Villevalde; A. N. Yakovlev; A. E. Soloveva; A. S. Alieva; N. G. Avdonina; E. A. Medvedeva; A. A. Fedorenko; V. V. Kulakov; V. A. Karlina; G. V. Endubaeva; et al. (Российский кардиологический журнал)
Cardiovascular morbidity and mortality are associated with high demographic and economic  losses.  Their decrease is one  of the  main lines of development  and improvement of the world health systems. An analysis of the current situation in the Russian  Federation  (RF) demonstrates that  the  areas  of concern  in system  for cardiovascular  diseases (CVD) patients’  care  are  the  insufficient and  untimely identification of cardiovascular risk factors, as well as their ineffective management due to the incomplete  implementation  of existing risk stratification guidelines and decision  making.  To achieve  the  aim of reducing  mortality from cardiovascular diseases by 2024 and further preserving of this tendency, along with the introduction of a  long-term  population-based strategy   for creating  a  healthy  lifestyle, it is necessary  to  shift  the  focus  from  emergency care  and  performing  high-tech interventions to long-term management of cardiovascular risks. The introduction of a new model of specialized care for cardiovascular diseases, the cardiovascular risk management system,  is aimed  at the  efficient use  of healthcare resources and providing the reduction in cardiovascular mortality.